2022
DOI: 10.1183/23120541.00046-2022
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia in critically ill patients with COVID-19 infection: a narrative review

Abstract: COVID pneumonitis can cause patients to become critically ill. They may require intensive care and mechanical ventilation. Ventilator-associated pneumonia is a concern. This review aims to discuss the topic of ventilator-associated pneumonia in this group. Several reasons have been proposed to explain the elevated rates of VAP in critically ill COVID patients compared to non-COVID patients. Extrinsic factors include understaffing, lack of PPE and use of immunomodulating agents. Intrinsic factors include severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…In addition, Giacobbe et al estimated the attributable mortality of VAP was about 50%, and patients showed a doubling in length of stay [ 11 ]. The rate of VAP recurrences varied from 23% to 37% according to studies comparing viral and non-viral ARDS [ 12 , 13 , 14 ]. Moreover, treatment failures occurred in up to 66% of COVID-19 patients under extracorporeal membrane oxygenation (ECMO) [ 15 ], and severe complications, such as lung abscesses, were frequently diagnosed [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Giacobbe et al estimated the attributable mortality of VAP was about 50%, and patients showed a doubling in length of stay [ 11 ]. The rate of VAP recurrences varied from 23% to 37% according to studies comparing viral and non-viral ARDS [ 12 , 13 , 14 ]. Moreover, treatment failures occurred in up to 66% of COVID-19 patients under extracorporeal membrane oxygenation (ECMO) [ 15 ], and severe complications, such as lung abscesses, were frequently diagnosed [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…111,112 In general, the rates of VAP in patients with COVID-19 who were critically ill was reported to rise above 50%, [113][114][115][116][117] with an estimated mortality exceeding 40%, and an increase in the number of patients requiring intensive care. 118 In a multicenter study, VAP accounted for 50% of all hospital-acquired infections in patients with COVID-19, with 28% prevalence of Gram-negative pathogens as agents in VAP. 119 In another case series, 2% of HAP and 33% of VAP were documented among COVID-19 patients admitted to the ICU, with VAP resulting in more acute respiratory distress syndrome (ARDS), and being associated with more acute kidney injury, long mechanical ventilation longer, and longer ICU stay.…”
Section: Carbapenem-resistant Enterobacterales (Cre)mentioning
confidence: 99%
“…Several studies have reported data on the epidemiology and consequences of bacterial VAP in patients with COVID-19 [ 5 7 ] or H1N1 influenza [ 8 ], most of which concerned risk factors, length of hospital stay and mortality [ 5 7 ]. Few comparisons were made between the two viruses regarding the occurrence of VAP.…”
Section: Introductionmentioning
confidence: 99%